You are on page 1of 6

Hypergeometric Functions

Reading Problems

Introduction
The hypergeometric function F (a, b; c; x) is dened as

F (a; b; c; x) =

2 F1 (a,

b; c; x) = F (b, a; c; x) x+ a(a + 1)b(b + 1) x2 c(c + 1) 2! +

= 1+

ab c

=
n=0

(a)n(b)n xn (c)n n!

|x| < 1, c = 0, 1, 2, . . .

where 2 1 refers to number of parameters in numerator refers to number of parameters in denominator

y1 = F (a, b; c; x) =

(c)

(a + n))(b + n) xn (c + n) n!

(a)(b) n=0

is one solution of the Hypergeometric Dierential Equation

x(1 x)y + [c (a + b + 1)x]y aby = 0 The other independent solution is

y2 = x1c F (a c + 1, b c + 1; 2 c; x)

c = 1, 2, . . .

Some Properties of F (a, b; c; x)


d dx F (a, b; c; x) = ab c F (a + 1, b + 1; c + 1; x)

The general formula based on repeated dierentiation

dk dxk

F (a, b; c; x) =

(a)k (b)k (c)k

F (a + k), b + k; c + k; x),

k = 1, 2, 3, . . .

Recurrence Relations
There are 15 recurrence relations, one of the simplest is

(a b)F (a, b; c; x) = aF (a + 1, b; c; x) bF (a, b + 1; c; x) See Abramowitz and Stegun for others.

Integral Representation
F (a, b; c; x) = (c) (b)(c b)
0 1

tb1 (1 t)cb1 (1 xt)a dt

|x| 1

Generating Function

w(x, t) = (1 t)bc (1 t + xt)b ,

c = 0, 1, 2, . . .

w(x, t) =
n=0

(c)n n!

F (n, b; c; x)tn

where F (n, b; c; x) denotes hypergeometric polynomials

F (n, b; c; x) =
i=0

(n) (b) xi (c) i!

<x<

Relation to Other Functions


Beta Functions xp p F (p, 1 q ; 1 + p; x)

Bx (p, q ) = B1 (p, q ) =

(p)(q ) (p + q )

Elliptic Integrals

K(k) =

1 1 , ; 1; k2 2 2

E(k) =

1 1 , ; 1; k2 2 2

Legendre Functions

P (x) = F

, + 1; 1;

1x 2

= integer

Q (x) =

1/2 ( + 1) 2 +1 ( +

3/2) x +1

1+ 3

3 1 1+ , ; + ; 2 2 2 2 x

| x| > 1

Chebyshev Polynomials

Tn(x) = F

n, n;

1 2

1x 2

Un(x) = (n + 1)F

n, n + 2;

3 2

1x 2

Bessel Function

J =

(x/2) ( + 1)

0 F1 + 1;

x2 4

Conuent Hypergeometric Functions (Kummers Function)


Functions M (a; c; x) and U (a; c; x)

M (a; c; x) =
n=0

(a)n xn (c)n n!

<x< c = 0, 1, 2 . . .

M (a; c; x) =

lim F (a, b; c; x/b)

also written as
1 F1 (a;

c; x)

Dierential Equation
xy + (c x)y ay = 0

If we change the variable to y = x1c z , then

xz

+ (2 c x)z (1 + a c)z = 0

where the solution is

z = M (1 + a c; 2 c; x) and

c = 2, 3, 4, . . .

y2 = x1c M (1 + a c; 2 c; x) is a second solution. Therefore the complete solution is y = y 1 + y2

c = 2, 3, 4, . . .

= C1 M (a; c; x) + C2 M (1 + a c; 2 c; x)

c = 0, 1, 2 . . .

Conuent Hypergeometric Function of the Second Kind

U (a; c; x) =

M (a; c; x)

sin c (1 + a c)(c)

x1c M (1 + a c; 2 c; x) (a)(2 c) c = 0, 1, 2. . . .

Integral Representations
(c) (a)(c a) 1 (a)
0 0 1

M (a; c; x) =

extta1 (1 t)ca1 dt

c>a>0

U (a; c; x) =

extta1 (1 + t)ca1 dt

a > 0, x > 0

with t = 1 u
1

M (a; c; x) = Therefore

(c) (a)(c a)

ex
0

exuuca1 (1 u)a1 du

M (a; c; x) = ex M (c a; c; x) for many other properties see Abramowitz and Stegun

Kummers Transformation

Relation to Other Functions


ex = M (a; a; x) 1 2 erfc(x) = ex U (a, x) = xa a 1 2 ; 1 2 ; x2

M (a; a + 1; x)

(a, x) = ex U (1 a; 1 a; x) 2 erf (x) = x M Jp (x) = (x/2)p (p + 1) (x/2)p (p + 1) 1 2 ; 3 2 ; x2 p+ 1 2 1 2 ; 2p + 1; 2ix

eix M ex M

Ip (x) =

p+

; 2p + 1; 2x

Kp (x) =

(2x)p ex U

p+

1 2

; 2p + 1; 2x 6